The essence of Bankim Chandra's Krishna Charitra - Caṭṭopādhyāẏa, Baṅkimacandra (Hindology Books, 2008)
section 1. The beginning -- section 2. Vrindavana -- section 3. Mathura to Dwaraka -- section 4. Indraprastha -- section 5. Upaplavya -- section 6. Kurukshetra -- section 7. The incidents in Prabhasha